2009
DOI: 10.1371/journal.pone.0007837
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNome Analysis Unravels the Molecular Basis of SARS Infection in Bronchoalveolar Stem Cells

Abstract: Severe acute respiratory syndrome (SARS), caused by the coronavirus SARS-CoV, is an acute infectious disease with significant mortality. A typical clinical feature associated with SARS is pulmonary fibrosis and associated lung failure. In the aftermath of the SARS epidemic, although significant progress towards understanding the underlying molecular mechanism of the infection has been made, a large gap still remains in our knowledge regarding how SARS-CoV interacts with the host cell at the onset of infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 64 publications
1
114
0
Order By: Relevance
“…Specifically, it has been reported that miR-223 plays a role in the pathogenesis of certain infectious diseases, such as influenza and chronic hepatitis B virus infection [23,25]. Moreover, an anti-viral effect for miR-223 was observed in SARS coronavirusinfected bronchoalveolar stem cells and in freshly isolated HIV-1-infected monocytes [24,30]. However, less is known about the roles of miRNAs, especially miR-223, in DENV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been reported that miR-223 plays a role in the pathogenesis of certain infectious diseases, such as influenza and chronic hepatitis B virus infection [23,25]. Moreover, an anti-viral effect for miR-223 was observed in SARS coronavirusinfected bronchoalveolar stem cells and in freshly isolated HIV-1-infected monocytes [24,30]. However, less is known about the roles of miRNAs, especially miR-223, in DENV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome (SARS), a twenty‐first‐century pandemic infection with typical clinical features of pulmonary fibrosis and lung failure that led to significant mortality, is caused by the coronavirus SARS‐CoV . Although SARS‐CoV cannot infect or replicate in fully differentiated cells, it is possible to study the virus in infected bronchoalveolar stem cells . Using this method, Mallick et al .…”
Section: Mir‐223 and Infectionmentioning
confidence: 99%
“…26 Some emerging evidences suggest that miRNAs may play an essential role in self-renewal and differentiation. [26][27][28][29][30][31][32] miRNAs are also harnessed in generating induced pluripotent stem cells (iPS cells). The mouse embryonic stem (ES) cell specific miRNAs-miR-291-3p, miR-294 and miR-295 helped in somatic cell reprogramming by enhancing the reprogramming efficiency of Klf4, Oct4 and Sox2.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%